How humans cooperate: confronting the challenge of collective action - Blanton, Richard E., author; Fargher, Lane F., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
A new approach to investigating human cooperation developed from the vantage point of an 'anthropological imagination.' Drawing the discipline's broad understanding of humans in biological, social, and cultural dimensions, and across a wide range of temporal, spatial, and cultural variation.--Provided by publisher.
What does evolutionary psychology tell us about human cooperation? -- The path to cooperation through collective action and institutions -- Anthropology: the missing voice in the conversation about cooperation -- The contingent cooperator as seen from the perspectives of neurobiology and bioevolution -- Cooperation or competition in the marketplace? -- On the need to rethink theories of state formation and how collective action theory will help -- Cooperation in state-building?: An investigation of collective action before and after the rise of modern democracies -- Center and hinterland under conditions of collective action -- Collective action and the shaping of cities and their neighborhoods -- The cultural process of cooperation -- The causes and consequences of collective action -- Final thoughts: insights gained from an expanded collective.
Keywords: Social action; Cooperation; Cooperativeness